Can austerity be self-defeating? - Daniel Gros; Rainer Maurer (Intereconomics, 2012)
With European governments cutting back on spending, many are asking whether this could make matters worse. In the UK for instance, recent OECD estimates suggest that 'austerity' will lead to another recession, which in turn may lead to a higher debt-to-GDP ratio than before. As the debate heats up, the following two articles attempt to provide some cool economic logic: Credible austerity plans are required by Daniel Gros and Why austerity can become self-defeating for member states of a currency union by Rainer Maurer.
Keywords: 330; Austeritätspolitik; Wirkungsanalyse; EU-Staaten